2019
DOI: 10.3390/molecules24193520
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Glycoconjugated LDH Inhibitors as Anticancer Agents

Abstract: Conjugation of known biologically active molecules to carbohydrate frameworks represents a valuable option for the preparation of hybrid, structurally-related families of compounds with the aim of modulating their biological response. Therefore, we present here a study on the preparation of d-galacto, d-manno, d-gluco, and d-lactose glycoconjugates of an established N-hydroxyindole-based (NHI) inhibitor of lactated dehydrogenase (LDH). Structural variations involved the sugar stereochemistry and size as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This compound was selective as LDHA inhibitor compares to its LDHB inhibitor activity (LDHB IC 50 value of 395.3 µM). These values were still higher compared to the IC 50 values of the GSK2837808A and GNE140 standards but lower compared to other established LDHA inhibitors, such as galloflavin, which was also used as a reference compound since it is routinely used in enzymatic LDH assays, with an IC 50 value of approximately 110 µM 29 . This result suggested that it could potentially become LDHA inhibitor drug candidate.…”
Section: Resultsmentioning
confidence: 82%
“…This compound was selective as LDHA inhibitor compares to its LDHB inhibitor activity (LDHB IC 50 value of 395.3 µM). These values were still higher compared to the IC 50 values of the GSK2837808A and GNE140 standards but lower compared to other established LDHA inhibitors, such as galloflavin, which was also used as a reference compound since it is routinely used in enzymatic LDH assays, with an IC 50 value of approximately 110 µM 29 . This result suggested that it could potentially become LDHA inhibitor drug candidate.…”
Section: Resultsmentioning
confidence: 82%
“…Particularly interesting is the protein-carbohydrate recognition, a phenomenon fundamental in many cellular mechanisms, such as migration, adhesion, cell-differentiation, tumor progression, infections (by viruses or bacteria), and immune response among others [ 59 , 60 , 61 , 62 , 63 ]. In the last years, the ubiquity but also the biological properties of glycoproteins or glycosylated natural products have driven research towards the synthesis of glycoconjugates for the development of drug candidates with anti-infectious, anti-inflammatory, anticancer, or vaccine activity [ 64 , 65 , 66 ].…”
Section: Carbohydrate-based Metzincin Inhibitorsmentioning
confidence: 99%